PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI PERBANDINGAN DI MTsN 6 TANAH DATAR - Rizal Mulya Arif; Kurnia Rahmi Y (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This research addresses the low ability of students to understand mathematical concepts, leading to difficulties in solving math problems. A significant factor contributing to this issue is the teaching materials that do not meet the needs and conditions of the learning environment. The study aims to develop interactive learning videos as an alternative teaching resource to enhance students' understanding of mathematical concepts. The research employs a research and development (R&D) method using the 4D model, which includes defining, designing, developing, and disseminating stages. However, the dissemination stage was not carried out due to time and budget constraints. The research instruments consist of validation sheets, practicality questionnaires, and tests of mathematical problem-solving abilities. Data analysis utilized percentage techniques and effectiveness measured through N-Gain calculations. The findings indicate that the developed interactive learning videos meet the criteria for validity, practicality, and effectiveness. The videos achieved a validity score of 87.67% (very valid), practicality scores of 87.85% from students and 94.17% from teachers (both very practical), and an N-Gain score of 0.61 (61%), indicating a good level of effectiveness in improving students' understanding of mathematical concepts.